SARS-CoV-2 pneumonia—receptor binding and lung immunopathology: a narrative review - Maria Clara Saad Menezes; Diego Vinicius Santinelli Pestana; Gustavo Rosa Gameiro; Luiz Fernando Ferraz da Silva; Ėlodie Baron; Jean-Jacques Rouby; José Otavio Costa Auler Jr (Critical Care, 2021)
Abstract The current pandemic of COVID-19 caused thousands of deaths and healthcare professionals struggle to properly manage infected patients. This review summarizes information about SARS-CoV-2 receptor binding dynamics and intricacies, lung autopsy findings, immune response patterns, evidence-based explanations for the immune response, and COVID-19-associated hypercoagulability.